Pricing of livestock products in Indonesian modern food retailers during covid-19 pandemic - Pambudy, R.; Adhi, A. K.; Herawati, H.; Harianto, H. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
The role of modern markets is increasing in the food system in Indonesia, mainly as a result of technological and institutional advances. Indonesian households' food consumption still depends on staple food. The share of household expenditure on meat, eggs, and milk was only 12 percent. The purpose of the study was to analyze the pricing of livestock products in retail level in the modern market.  The data used in this study is daily price data for beef, eggs, and chicken at wholesale and retail levels published through the National Strategic Food Price Information Center (PIHPSN) from January 2020 to December 2020.  This study employed a quantitative method, through the formulation of an econometric model, and applied the 3SLS method to estimate the model.  The results show that traders face an increasing price risk following the Covid-19 pandemic.  The retailers enforce price stabilization at the consumer level when prices at the wholesaler level fluctuate. However, the study did not find the practice of price averaging between commodities at the retailers level.  The results of this study are useful for policy formulations aimed at stabilizing food prices.